The efficacy of radioactive iodine for the treatment of well-differentiated thyroid cancer with distant metastasis. Issue 12 (December 2018) - Lin, Jen-Der; Kuo, Sheng-Fong; Huang, Bie-Yui; Lin, Shu-Fu; Chen, Szu-Tah
Abstract : Objective: Radioactive iodine ( 131 I) has been used as a treatment for high-risk well-differentiated thyroid cancer after thyroidectomy. The aim of this study was to evaluate the long-term follow-up results after using high accumulated doses of 131 I (>600 mCi) for the treatment of well-differentiated thyroid cancer. Patients and methods: In this study, we retrospectively evaluated prospectively enrolled patients with well-differentiated thyroid cancer who were treated and followed up in Chang Gung Memorial Hospital in Linkou and Keelung, Taiwan. All the patients underwent thyroidectomy between 1979 and 2016. Results: For our study, 228 patients with papillary and follicular thyroid carcinoma with distant metastases were enrolled. Of the 228 patients, 71 (31.1%) received 131 I therapy with an accumulated dose of at least 600 mCi. Forty-four died because of disease-specific mortality (DSM) after a mean follow-up of 10.6±6.3 years. Compared with the patients in the DSM group, which included 27 survival cases, patients who were younger, and those with a multifocal tumor, more extensive thyroidectomy, and papillary thyroid carcinoma showed better prognosis. The DSM group included a higher percentage of patients who developed a secondary primary cancer after receiving a diagnosis of thyroid cancer than the survival group (18.2 vs. 3.7%). However, the difference did not reach statistical significance ( P =0.075). Conclusion: 131 I provided an effective therapeutic modality for well-differentiated thyroid cancer patients with distant metastasis. After a mean of follow-up 10 years, more than 60% of cases resulted in DSM when high accumulated 131 I doses were administered.